Hybrid dual-network hydrogel for 3D printing as well as preparation method and application of hybrid dual-network hydrogel
The hybrid dual network hydrogel precursor solution prepared by predissolving the problem of insufficient mechanical properties of the hydrogel and difficulty in dissolution of photoinitiators, and realizes a 3D printed hydrogel with high mechanical strength, conductivity and transparency, suitable for the manufacturing of flexible electronic devices.
Patent Information
- Application Number
- CN202411435920.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-25
AI Technical Summary
In processing and application, existing hydrogels have problems such as low mechanical strength, complex processing methods, and unstable performance. Especially in 3D printing technology, the mechanical properties of photocured hydrogels are insufficient and it is difficult to achieve effective dissolution of high-efficiency photoinitiators.
The hybrid double network hydrogel precursor solution is prepared by predissolving the photoinitiator through the cross-linking agent as the intermediate solvent to form an intermediate solution, and then dissolve it in the acrylamide aqueous solution and chitosan acrylic acid aqueous solution to achieve a dual cross-linking reaction to prepare a strong hybrid double network hydrogel.
实现了高机械强度、导电性好、透明度高的3D打印水凝胶,简化了加工工艺,提高了打印速度和成本效益,并适用于柔性电子器件和智能柔性机器人的制造。
Smart Images

Figure CN119505091A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a 3D printed hybrid double network hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogels are usually generated by simple reactions of one or more monomers. They are known for their internal three-dimensional network structure and high water content, and have highly designable structural and functional diversity. Therefore, hydrogels have been widely used in soft robotics, flexible electronics, biosensors, and drug delivery. Despite these multifunctional properties, hydrogels still expose some serious defects in practical applications, among which the lack of efficient processing methods and low mechanical strength are two prominent problems.
[0003] Traditional hydrogel processing methods, such as mold casting, have technical problems including: first, the process is complex and time-consuming; mold casting involves multiple steps, the entire process is lengthy, and it is difficult to meet the needs of rapid production or small batch customization. Second, the degree of customization is low; the mold design limits the flexibility of the product, and the design modification requires remaking the mold, which increases the cost and time; finally, the prepared hydrogel has unstable performance; the fluidity of the materials used to prepare hydrogels in the prior art and the cross-linking reaction may be uneven, resulting in fluctuations in the mechanical and physical properties of the hydrogel, thereby affecting the quality of the hydrogel product and the reliability of use.
[0004] Compared with the above-mentioned existing technologies, three-dimensional (3D) printing technology may be an effective alternative. The layer-by-layer solidification of hydrogel precursors can achieve high-precision and customized manufacturing of complex hydrogel structures, and can ensure the consistency of the mechanical properties of the entire structure, while reducing material waste and shortening manufacturing time.
[0005] However, most existing photocurable hydrogels are formed by the polymerization of low molecular weight monomers, which often leads to dense cross-linked networks, making the hydrogel structure fragile. On the other hand, commonly used hydrogel material systems, such as photocurable acrylic acid (AA) / polyvinyl alcohol (PVA) and acrylamide (AM)-polyethylene glycol (PEG) diacrylate hydrogels, show insufficient strength and extremely low Young's modulus due to their single and loose cross-linked networks. Therefore, double network (DN) hydrogels are composed of two intertwined cross-linked networks with high strength and toughness. Hybrid double network hydrogels (Hybrid DN hydrogels) are a special double network hydrogel that combines a strong chemical cross-linked network with a flexible physical cross-linked network. Among them, the chemical cross-linked network formed by intermolecular covalent bonds creates a highly cross-linked strong network that helps dissipate energy during loading. Repairable low-strength physical cross-linked networks, such as hydrogen bonds and metal coordination bonds, are introduced as "sacrificial bonds" that can effectively dissipate stress energy and further enhance the strength and toughness of the hydrogel. In addition, the double network hydrogel is compatible with photocuring 3D printing technology. For example, some studies have used photocuring 3D printing technology to prepare strong hydrogels, which greatly improved the mechanical properties of hydrogels and broadened their application areas. For specific application studies, see M. Hua, et al. ACS Appl Mater Interfaces 2021, 13, 12689.; H. Yang, et al. Matter 2021, 4, 1935.; Z. Sun et al., Addit Manuf 2022, 50, 102563; Y. Wang, et al., Chemical Engineering Journal 2023, 457, 141268. However, the above-mentioned method of enhancing the mechanical properties of 3D printed hydrogels usually involves a post-processing step, that is, immersing the printed sample in a solution containing specific ions to form a metal coordination bond, which requires the fragile hydrogel to be transferred to the post-processing solution. This process can easily lead to undesirable expansion or contraction of the hydrogel, which inevitably causes deformation and leads to a decrease in mechanical properties. In addition, the post-processing steps may also lead to inconsistent mechanical properties of hydrogels due to uneven penetration of metal ions.
[0006] In addition, photocuring-based 3D printed hydrogels usually contain up to 30% to 90% water, so all components including monomers, crosslinkers and photoinitiators must be completely dissolved in water. However, traditional high-efficiency photoinitiators, such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO) and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO), are difficult to dissolve in water, while some water-soluble photoinitiators (e.g., 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (I2959), 2,2'-azobis(2-guanidinopropane) dihydrochloride (V50)) show low curing efficiency, requiring extremely high exposure power and long curing time, which significantly reduces printing accuracy and increases manufacturing time. Therefore, achieving effective dissolution of high-efficiency photoinitiators in hydrogel precursors remains a key challenge in the photocuring 3D printing process of photocurable hydrogels. Summary of the invention
[0007] Purpose of the invention: The technical problem to be solved by the present invention is to provide a hybrid double network hydrogel precursor solution and its preparation method and application.
[0008] The technical problem that the present invention also aims to solve is to provide a hybrid double network hydrogel and a preparation method and application thereof.
[0009] The technical problem that the present invention also solves is to provide a 3D printed strong double network hydrogel with high mechanical strength, good conductivity, high transparency, simple processing technology, fast printing speed and low cost, as well as a preparation method and application thereof.
[0010] The technical problem that the present invention also solves is to provide a 3D printed strong double network hydrogel and its preparation method for use in the preparation of flexible electronic devices.
[0011] The final technical problem to be solved by the present invention is to provide a flexible actuator.
[0012] Technical solution: In order to solve the above technical problems, the present invention provides a method for preparing a precursor solution of a hybrid double network hydrogel, wherein the precursor solution is prepared by a pre-dissolution method; the pre-dissolution method comprises using a cross-linking agent as an intermediate solvent to dissolve a photoinitiator to form an intermediate solution, and then dissolving the intermediate solution in an acrylamide-based aqueous solution and an acrylic acid aqueous solution of chitosan to obtain the precursor solution.
[0013] The photoinitiator includes one or more of 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide (BAPO) or 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173); the cross-linking agent includes one or more of polyethylene glycol diacrylate (PEGDA), hydroxyethyl methacrylate (HEMA), Pluronic F127-diacrylate (PF127-DA) or hyaluronic acid methacrylate (Hyaluronic acidmethacrylate, HAMA); and the water content of the precursor solution is 30 to 80 wt%.
[0014] Furthermore, the method for preparing the precursor solution of the hybrid double network hydrogel of the present invention specifically comprises the following steps:
[0015] (1) dissolving acrylamide monomers in an aqueous solution of an inorganic zirconium compound to form an acrylamide aqueous solution, referred to as solution a;
[0016] (2) dissolving chitosan and acrylic acid in water, referred to as solution b;
[0017] (3) mixing the PEGDA and the TPO evenly to form an intermediate solution, referred to as solution c;
[0018] (4) Under stirring conditions, the solution b and the solution c are added to the solution a and mixed evenly to obtain the precursor solution.
[0019] The acrylamide-based aqueous solution is obtained by dissolving acrylamide monomers in an inorganic zirconium compound aqueous solution, wherein the acrylamide monomers include acrylamide and / or acrylamide derivatives, wherein the acrylamide derivatives include any one of N,N-diethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-isopropylacrylamide, N-isobutylacrylamide, N-tert-butylacrylamide and N-cyclohexylacrylamide, and the inorganic zirconium compound is any one of zirconium oxychloride, zirconium tetrachloride, zirconium sulfate and zirconium nitrate. Preferably, the inorganic zirconium compound in the inorganic zirconium compound aqueous solution is The weight ratio of water is 1:20 to 1:4. Preferably, the weight ratio of the acrylamide monomer to water is 1:4 to 7:3; preferably, the weight ratio of chitosan to the acrylamide monomer is 1:1000 to 1:50; preferably, the weight ratio of acrylic acid to the acrylamide monomer is 1:100 to 1:1, preferably, the weight ratio of polyethylene glycol diacrylate to the acrylamide monomer is 1:100 to 1:20, preferably, the weight ratio of polyethylene glycol diacrylate to 2,4,6-trimethylbenzoyldiphenylphosphine oxide is 10:1 to 50:1. Preferably, the concentration of the zirconium nitrate aqueous solution is 0.12 mol / L to 0.47 mol / L.
[0020] Wherein, the weight ratio of the solution a, the solution b and the solution c is 120:10:1.
[0021] The present invention also includes a precursor solution prepared by the method for preparing a precursor solution of the hybrid double network hydrogel.
[0022] The present invention also includes the use of the precursor solution in preparing a hybrid double network hydrogel.
[0023] The present invention also includes a hybrid double network hydrogel, wherein the hybrid double network hydrogel adopts the precursor solution as described above to carry out a double cross-linking reaction through a one-pot method to obtain the hybrid double network hydrogel. Preferably, the double cross-linking reaction includes forming a primary network through a chemical cross-linking reaction between an acrylamide monomer and a cross-linking agent under ultraviolet light irradiation; constructing a secondary network with chitosan; and establishing an in-situ physical cross-linking reaction between an inorganic zirconium compound and the secondary network to form the hybrid double network hydrogel.
[0024] The present invention also includes a one-step method for preparing a 3D printed double network hydrogel, wherein the precursor solution as described is subjected to photocuring 3D printing to obtain a 3D printed double network hydrogel; the 3D printed double network hydrogel is customized in pattern or shape to obtain a hydrogel sample, and preferably, the method also includes adding a transparent dye to the precursor solution; preferably, the transparent dye is a water-soluble dye; preferably, the transparent dye is lemon yellow or methylene blue; preferably, the amount of the transparent dye added is 0.01 to 0.05 wt% of the hydrogel precursor solution; preferably, the photocuring 3D printing includes printing layer by layer using a photocuring 3D printer; preferably, the photocuring 3D printing includes but is not limited to SLA (stereolithography) printing, DLP (digital light processing) printing, LCD (liquid crystal display) printing, CLIP (continuous liquid surface generation) printing, TPP (two-photon polymerization) printing, PμSL (projection micro-stereolithography) printing, etc.
[0025] In some preferred embodiments, the photocuring 3D printing adopts DLP printing technology, and uses a bottom-up projection method to print layer by layer on a 3D printer; the printing parameters for each layer of curing are set as follows: layer height 100 μm, exposure time 3 s, exposure power density 30 mW / cm 2 , the printing speed is 0.7~4s / 100μm.
[0026] In some preferred embodiments, the light-curing 3D printing adopts DLP printing technology, and uses a bottom-up projection method to print layer by layer on a 3D printer; the printing parameters for each layer of curing are set as follows: layer height 100 μm, exposure time 0.7 s, exposure power density 7 mW / cm 2 , the printing speed is 0.7~4s / 100μm.
[0027] As a preferred embodiment, the preparation method further includes adding a transparent dye to the hydrogel precursor solution to prevent light scattering and improve printing accuracy. The printing parameters for each layer of curing are set as follows: layer height 100 μm, exposure time 3 s, exposure power density 30 mW / cm 2 .
[0028] The present invention also includes a 3D printed hybrid double network hydrogel, which is prepared by the preparation method as described; the 3D printed hybrid double network hydrogel has a breaking stress of 0.51-7.25 MPa, a breaking elongation of 475-680%, a Young's modulus of 0.31-1.73 MPa, a toughness of 1.82-15.85 MJ / m3, a conductivity of 0.75-0.90 S / m, and a transparency of ≥90%.
[0029] The present invention also includes a method for preparing the precursor solution, the precursor solution, the hybrid double network hydrogel, a method for 3D printing the double network hydrogel, and an application of the 3D printed hybrid double network hydrogel in preparing flexible electronic devices, wherein the flexible electronic devices include flexible sensors, flexible actuators, and flexible robots.
[0030] The present invention also includes a flexible actuator, which is prepared by the preparation method of 3D printing hybrid double network hydrogel as described above; the flexible actuator includes a customizable flexible sensor, a solvent-induced shape memory actuator and a self-sensing pneumatic actuator.
[0031] As a preferred embodiment, the solvent-induced shape memory actuator can grasp objects by changing its shape in a solvent; specifically, the initial shape of the flexible actuator is a grasping state, and it is transformed into an open state and immersed in isopropyl alcohol (IPA) for 3 minutes to fix its shape; when the flexible actuator is immersed in water, it will be reactivated and slowly restore the grasping shape to grasp underwater objects; the entire grasping process is completed in about 10 seconds.
[0032] As a preferred embodiment, when a gravity load is applied or positive / negative air pressure is filled, the self-sensing pneumatic actuator (pneumatic muscle) will be caused to extend / contract. During this process, the deformation of the self-sensing pneumatic actuator causes a change in resistance. Therefore, the movement state of the pneumatic muscle is monitored in real time by measuring the change in the resistance value of the self-sensing pneumatic actuator; and the above-mentioned extension / contraction has good repeatability and consistency.
[0033] Mechanism of the present invention: The present invention proposes a "pre-dissolution" method of using PEGDA to dissolve TPO photoinitiator. This intermediate solution can be fully dissolved in an acrylamide-based aqueous solution to form a precursor solution. The pre-dissolution method not only effectively solves the technical problem that the high-efficiency photoinitiator TPO is difficult to dissolve in a precursor solution with a high water content; moreover, the obtained precursor solution can undergo a rapid double cross-linking reaction (chemical cross-linking and physical cross-linking) under ultraviolet light irradiation to obtain a strong and tough hybrid double network hydrogel, which solves the problem of poor mechanical properties of the hydrogel and is mixed with an acrylamide aqueous solution to prepare a photocurable hydrogel; through ultraviolet irradiation in photocurable 3D printing, Zr-containing hydrogels are synthesized in situ. 4+The double network hydrogel cross-linked by coordination bonds and covalent bonds realizes one-step 3D printing of strong and tough double network hydrogel; at the same time, the hydrogel can be applied to technologies such as flexible sensors, shape memory actuators and self-sensing pneumatic actuators. In addition, the present invention pours the precursor solution into the resin tank of the 3D printer, and uses the "bottom-up" projection method to print the hydrogel layer by layer on the DLP (digital light processing, a type of VPP technology) 3D printer. During the 3D printing process, the photoinitiator generates free radicals under the excitation of ultraviolet light, and the free radicals attack the C=C double bonds in AM (acrylamide), AA (acrylic acid), and PEGDA to form a chemically cross-linked P (AM-co-AA) network. The cross-linking agent PEGDA provides chemical cross-linking sites between copolymer chains in this chemical reaction. At the same time, the large number of reaction sites on the rigid chitosan (CS) molecular chain provides a broad space for the design and construction of hydrogel networks. Due to the similarity of chemical composition with biological systems, hydrogels composed of natural polymers usually have good biocompatibility with the human body. In addition, especially its characteristics of degradation in the body make it an important component of biocompatible conductors or flexible electronic devices in the field of biosensing. The amino, hydroxyl and carboxyl groups in the rigid chitosan (CS) chain and the soft copolymer P (AM-co-AA) chain form a large number of hydrogen bonds. In addition, the in situ Zr 4+ Coordinate bonds are formed with the carboxyl and amino groups of the CS chains and P(AM-co-AA) chains. Therefore, the CS and P(Am-co-AA) molecular chains exhibit two different types of physical interactions, including hydrogen bonds and metal coordination bonds. The non-covalent interactions provide physical cross-linking sites for the hydrogels, facilitating the rapid solid-liquid separation of the polymers without the need for excessive initiators and cross-linkers. The photocurable hydrogels exhibit excellent mechanical properties due to the dynamic dual physical synergy and covalent cross-linking.
[0034] Beneficial effects: Compared with the prior art, the advantages of the present invention include:
[0035] 1. The double cross-linking mechanism of the present invention prepares a hybrid double network hydrogel in one step by preparing a precursor solution with a high water content and combining it with 3D printing technology for photocuring cross-linking reaction. The method is simple and universal. The obtained hybrid double network hydrogel has excellent mechanical properties, high transparency, high conductivity and rapid printing capability, so that it can be used in the field of sensors and actuators, including customizable flexible sensors, solvent-induced shape memory actuators and self-sensing pneumatic actuators, laying the foundation for the efficient manufacturing of flexible electronic devices and intelligent flexible robots.
[0036] 2. The double cross-linking mechanism of the present invention includes the dual effects of covalent cross-linking and non-covalent cross-linking. The prepared hydrogel has extremely strong mechanical properties, and the precursor solution can achieve rapid solid-liquid separation under ultraviolet light irradiation, with a water content of up to 80%.
[0037] 3. The present invention adopts a cross-linking agent pre-dissolution method, pre-dissolving the photoinitiator (TPO) in the cross-linking agent (PEGDA) to form a mixed solution, and then dissolving the mixed solution in an acrylamide-based aqueous solution with a high water content (up to 80wt%). This not only allows TPO to be completely dissolved in the acrylamide-based aqueous solution with a high water content, but also allows the cross-linking reaction of the double network to be conducted without excessive cross-linking agents and other special water-soluble photoinitiators, thereby solving the problem in the prior art that high-efficiency photoinitiators (such as TPO) are difficult to apply to 3D printing technology due to their poor water solubility and only being slightly soluble in water or insoluble in water.
[0038] 4. The present invention adopts a one-step method to directly prepare a 3D printable double-network hydrogel with strong mechanical properties, transparency and conductivity through a precursor solution. In particular, high-precision photocuring printing can be performed, overcoming the shortcomings of traditional hydrogels being soft and brittle. The whole process is simple and does not require complicated preparation technology. At the same time, it is suitable for cheap and efficient commercial photoinitiators (TPO), avoiding complicated preparation or purchasing inefficient and expensive water-soluble photoinitiators, saving time and economic costs. The prepared hydrogel has excellent adjustable mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the one-step method for preparing strong and tough hybrid double network hydrogel based on DLP 3D printing in the present invention.
[0040] Figure 2 These are Fourier transform infrared spectra (FTIR) of the hydrogel sample (P(AM-AA)+CS+Zr) prepared in Example 1 of the present invention, as well as PAM, P(AM-AA), and P(AM-AA)+CS.
[0041] Figure 3 Hydrogel sample physical picture, transparency comparison chart and infrared spectrum transmittance chart; Figure 3 a is a physical picture of hydrogel samples of different geometric shapes 3D printed in Example 5 of the present invention; Figure 3 b and Figure 3 c are the actual pictures of hydrogel samples with different geometric shapes 3D printed in Example 1 of the present invention; Figure 3 d is a transparency comparison diagram of the hydrogel samples of Example 1 and Example 5 of the present invention; Figure 3 e is the infrared spectral transmittance diagram of the hydrogel samples of Examples 1 and 5 of the present invention.
[0042] Figure 4 These are comparison diagrams of the effects of different zirconium ion concentrations on the mechanical properties of hydrogels; Figure 4 a is a comparison of stress-strain curves of hydrogels containing different zirconium ion concentrations. Figure 4 b is a comparison chart of toughness and Young's modulus at different zirconium ion concentrations; Figure 4 c is a comparison chart of elongation at break and breaking strength;
[0043] Figure 5 Comparison of the mechanical properties of hydrogels prepared from precursor solutions with different water contents.
[0044] Figure 6 They are respectively the mechanical cyclic stability analysis diagrams of the hydrogel samples of Example 1 of the present invention.
[0045] Figure 7 This is a physical picture of the 3D printed hydrogel strain sensor of Example 1 of the present invention.
[0046] Figure 8 This is a result diagram of relevant performance parameters of the hydrogel product of Example 1 of the present invention as a sensor, Figure 8 a is a graph showing the change in relative resistance of the hydrogel sample used as a sensor as a function of mechanical strain in Example 1 of the present invention;
[0047] Figure 8 b is a performance change diagram of the hydrogel sensor of Example 1 of the present invention after 130 loading-unloading cycles; Figure 8 c- Figure 8 f are real-time changes in relative resistance of the hydrogel samples printed in Example 1 of the present invention as hydrogel strain sensors during bending at different angles of the finger, wrist, elbow joint, and knee joint.
[0048] Fig. 9 Schematic diagram of the working principle of the hydrogel sample printed in Example 1 of the present invention as a solvent-actuated hydrogel.
[0049] Fig.10 This is a working principle diagram of the hydrogel sample of Example 1 of the present invention as a self-sensing pneumatic actuator.
[0050] Fig.11 This is a comparison chart of the experimental effects of the direct dissolution method and the pre-dissolution method in Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is described in further detail below.
[0052] Figure 1 The schematic diagram of the present invention is a one-step method for preparing a strong and conductive double network hydrogel based on DLP 3D printing. Figure 1It can be seen that the present invention dissolves acrylamide monomers in an inorganic zirconium compound solution to form solution a; dissolves chitosan and acrylic acid in water to form solution b; mixes the crosslinking agent and the photoinitiator evenly to form solution c; and under stirring, adds the solution b and the solution c to the solution a to form a precursor solution.
[0053] Furthermore, under ultraviolet light irradiation, the photoinitiator generates free radicals under the excitation of ultraviolet light, and the crosslinker PEGDA provides chemical crosslinking sites between copolymer chains in the chemical reaction. The free radicals attack the C=C double bonds in AM, AA, and PEGDA, and a rapid chemical crosslinking reaction occurs to form a primary network (P(AM-co-AA) network); at the same time, the amino, hydroxyl, and carboxyl groups in the rigid chitosan (CS) chain and the copolymer P(AM-co-AA) chain form a large number of hydrogen bonds, and the in situ Zr 4+ The Zr 4+ The metal coordination bonds and hydrogen bonds establish in-situ physical crosslinks with the second network (CS), forming a hybrid double network hydrogel under the dual effects of covalent crosslinking and non-covalent crosslinking. The hybrid double network hydrogel obtained by the above reaction not only exhibits extremely strong mechanical properties, but also can achieve rapid solid-liquid separation (up to 80% water content) during DLP printing, without the need for excessive crosslinking agents and special water-soluble photoinitiators.
[0054] The precursor solution is poured into the printer resin tank, and the hydrogel is printed layer by layer on the DLP 3D printer using a "bottom-up" projection method. During the 3D printing process, the photoinitiator generates free radicals under the excitation of ultraviolet light, and the free radicals attack the C=C double bonds in AM, AA, and PEGDA to form a chemically cross-linked P (AM-co-AA) network. The cross-linking agent PEGDA provides chemical cross-linking sites between copolymer chains in this chemical reaction. At the same time, a large number of hydrogen bonds are formed between the amino, hydroxyl, and carboxyl groups in the rigid chitosan (CS) chain and the copolymer P (AM-co-AA) chain; in addition, the in situ Zr 4+ Coordinate bonds are formed with the carboxyl and amino groups of the CS chains and P(AM-co-AA) chains. Therefore, the CS and P(AM-co-AA) molecular chains exhibit two different types of physical interactions, including hydrogen bonds and metal coordination bonds. The photocurable hydrogels exhibit excellent mechanical properties due to the dynamic dual physical synergy and covalent crosslinking.
[0055] The present invention adopts a pre-dissolution method to prepare a precursor aqueous solution containing a high-efficiency photoinitiator TPO, and can prepare a hydrogel sample by 3D printing in a one-step method. Based on its excellent mechanical properties and conductivity, it can be applied to flexible electronic devices, including but not limited to flexible sensors, flexible actuators and flexible robots.
[0056] For the convenience of description, the hybrid double network hydrogel is abbreviated as PZC hydrogel hereinafter.
[0057] In the embodiments listed in the present invention, DLP printing technology is used as an example for explanation, and the same technical effect can also be achieved by using other photocuring 3D printing methods; in addition to DLP (digital light processing) printing, photocuring 3D printing also includes SLA (stereolithography) printing, LCD (liquid crystal display) printing, CLIP (continuous liquid surface generation) printing, TPP (two-photon polymerization) printing, PμSL (projection micro-stereolithography) printing, etc., but is not limited to these.
[0058] In a specific embodiment of the present invention, the printer used to prepare the 3D printed hydrogel sample is a commercial desktop DLP3D printer (MAX X27, Asiga, US) to print the 3D structure, and the wavelength of the light source is 405nm, which is in the ultraviolet range. For the hydrogel provided by the present invention, which is a transparent ion composite hydrogel, for the hydrogel sample without dye, a shorter exposure time is selected, t = 0.7s / 100μm, and the exposure power density is 7mW / cm 2 , higher resolution objects can be obtained; introducing dyes (such as lemon yellow) into the precursor solution can prevent light scattering and further improve the printing resolution. The amount of lemon yellow added is 0.05wt% of the precursor solution, and the printing parameters are: layer height 100μm, exposure time 3s, exposure power density 30mW / cm 2 .
[0059] The printed model was designed by AutoCAD (2021) and digitally sliced by Asiga Composer software. The design of the model does not fall within the scope of the present invention.
[0060] Example 1
[0061] 1. Preparation of PZC hydrogel sample (P(AM-AA)+CS+Zr):
[0062] 1) Dissolve 120 g of acrylamide (AM) and 12 g of zirconium nitrate pentahydrate (Zr(NO3)4·5H2O) in 120 g of deionized water, stirring continuously, and mark it as solution a.
[0063] 2) Add 0.5 g chitosan (CS) and 5 g acrylic acid (AA) into 50 g deionized water and mix them, which is marked as solution b.
[0064] 3) Mix 10 g of PEGDA (Mw (weight-average molecular weight) = 700) (McLean CAS: 26570-48-9, Part No.: P816111-100m) and 1 g of photoinitiator TPO to form a PEGDA solution, marked as solution c.
[0065] 4) Under rapid stirring, 12g solution b, 1.2g solution c and 0.1g lemon yellow were added to 252g solution a to form a precursor solution; the addition amount of each reactant in this embodiment is shown in Table 1, wherein the zirconium ion concentration is 0.23mol / L, the water content of the precursor solution is shown in Table 2, which is 134.64g, and the water content of the precursor solution is about 50wt%.
[0066] 5) Pour the precursor solution into the resin tank of the DLP printer to print a strong hydrogel sample.
[0067] 2. Preparation of PAM hydrogel:
[0068] 12 g of acrylamide (AM) was dissolved in 12 g of deionized water, and 0.12 g of the solution c in step 3) of the PZC hydrogel sample preparation was added, and a hydrogel was formed after ultraviolet light irradiation.
[0069] 3. Preparation of P(AM-AA) hydrogel:
[0070] 1) Dissolve 12 g of acrylamide (AM) in 12 g of deionized water with continuous stirring, labeled as solution a.
[0071] 2) 1.2 g of acrylic acid (AA) and 0.12 g of solution c in step 3) of the PZC hydrogel sample preparation were added to solution a in step 1) and mixed evenly, and a hydrogel was formed after irradiation with ultraviolet light.
[0072] 4. Preparation of P(AM-AA)+CS hydrogel
[0073] 1) Dissolve 12 g of acrylamide (AM) in 12 g of deionized water with continuous stirring, labeled as solution a.
[0074] 2) 0.5 g chitosan (CS) and 5 g acrylic acid (AA) were added to 50 g deionized water and mixed, which was marked as solution b.
[0075] 3) 1.2 g of solution b and 0.12 g of solution c in step 3) of the PZC hydrogel sample preparation were added to solution a and mixed evenly, and a hydrogel was formed after irradiation with ultraviolet light.
[0076] See also Figure 2The displacement of the characteristic peak positions of the PZC hydrogel samples (P(AM-AA)+CS+Zr)), PAM, P(AM-AA), and P(AM-AA)+CS prepared in this example was compared by Fourier transform infrared spectroscopy (FTIR). The typical characteristic peak positions of the carboxyl, carbonyl, hydroxyl, and amide groups in PZC were shifted to 1424 cm -1 、1651cm -1 、3334cm -1 and 3185cm -1 , which indicates the formation of metal coordination bonds.
[0077] See also Figure 3 b and Figure 3 c are actual pictures of 3D structures of hydrogel samples with different geometric shapes printed by 3D printer using the PZC hydrogel samples prepared in this example. Figure 3 b shows the printed PZC hydrogel samples, such as octahedral lattices, carbon nanotubes, buckyballs, and octopuses. Figure 3 c shows the large structures of printed PZC hydrogel samples, such as ears and buildings. As can be seen from the figure, the different samples printed have high printing accuracy.
[0078] See also Figure 6 a is a graph showing the change in tensile strength of the PZC hydrogel printed in this example under different tensile strains; Figure 6 b is the tensile strength curve of the PZC hydrogel printed in this embodiment after 300 cycles of stretching with 100% strain; Figure 6 c is the energy dissipation and dissipation rate of the PZC hydrogel printed 300 times in this embodiment. As can be seen from the figure, the PZC hydrogel provided in this embodiment has the characteristics of cyclic stability and anti-fatigue. Figure 7 , a sample picture of the printed PZC hydrogel customized strain sensor. Figure 8 a- Figure 8 f are the changes in the sensing performance of the printed PZC hydrogel strain sensor. Figure 8 a is the relative resistance of the PZC hydrogel sensor changing with mechanical strain; Figure 8 b Relative resistance change of PZC hydrogel sensor under 130 loading-unloading cycles with a maximum strain of 40%. Figure 8 c- Figure 8 f is the relative resistance change of the PZC hydrogel as a strain sensor during the bending of the finger, wrist, elbow, and knee at different angles. As can be seen from the figure, as the bending angle of each joint increases, the change in the relative resistance of the sensor also increases accordingly, indicating that the printed PZC hydrogel sensor can monitor the motion state of each joint in real time by measuring the relative resistance change. Fig. 9, is a schematic diagram of the working principle of the 3D printed solvent-driven PZC hydrogel as a shape memory soft actuator in this embodiment. Specifically, the printed solvent-driven actuator has an initial shape of a grasping state (see Fig. 9 a), then the actuator is transformed into the open state and immersed in isopropyl alcohol (IPA) for 3 minutes to fix its shape (see Fig. 9 b). When the actuator is immersed in water, it will reactivate and slowly restore the grasping form to grasp the underwater object (see Fig. 9 c~ Fig. 9 f). The whole crawling process is very fast and is completed in about 10 seconds.
[0079] See also Fig.10 , the PZC hydrogel sample printed in this embodiment is used as a self-sensing pneumatic actuator, where Fig.10 a~ Fig.10 d is a schematic diagram of the working principle of the 3D printed pneumatic stretchable self-sensing artificial muscle. When a load is applied to the pneumatic muscle, the pneumatic muscle is stretched due to gravity, and the overall resistance of the pneumatic muscle increases. Fig.10 As shown in FIG. 4 , the stretching distance and resistance change of the pneumatic muscle increase linearly with the increase of the load weight. Therefore, it can be inferred that the pneumatic muscle can sense the weight of the added load. Fig.10 c and Fig.10 d, respectively, the extension / contraction of the pneumatic muscle caused by the positive / negative air pressure. During this process, Fig.10 As shown in f, the change in resistance caused by the deformation of the pneumatic muscle has good repeatability and consistency. Obviously, the movement state of the pneumatic muscle can be monitored in real time by measuring the change in the resistance value of the pneumatic muscle. See Table 3 for the mechanical properties, conductive properties, and transparency test results of the PZC hydrogel samples prepared in this embodiment. The test method is referenced (3D Printing of Strong and Tough Double Network GranularHydrogels, Adv. Funct. Mater. 2021, 31, 20059).
[0080] Effect of the concentration of zirconium nitrate in Examples 2 to 4 and Comparative Example 1 on the mechanical properties of PZC hydrogel
[0081] The difference between Examples 2 to 4 and Example 1 is that the concentration of zirconium nitrate is different. The concentrations of zirconium nitrate aqueous solutions in Examples 2 to 4 are 0.12 mol / L, 0.35 mol / L, and 0.47 mol / L, respectively; the other steps are the same. The difference between Comparative Example 1 and Example 1 is that the solution a in step 1 does not include zirconium ions, and the other steps are the same.
[0082] The differences in specific zirconium ion concentrations of Examples 2-4 are shown in Table 1.
[0083] Table 1: Precursor formula for studying the effect of zirconium ion concentration on the mechanical properties of PZC hydrogels
[0084]
[0085]
[0086] The results are shown in Table 3, which are the test results of mechanical properties, conductive properties, and transparency of the hydrogel samples prepared in Examples 2 to 4.
[0087] Example 5
[0088] The only difference between this embodiment and embodiment 1 is that no transparent dye is added to the precursor solution; the other steps are the same.
[0089] See also Figure 3 a, are dye-free hydrogel samples printed in this embodiment, which are butterfly, microneedle, pyramid, and negative Poisson's ratio lattice; compared with the hydrogel sample with lemon yellow added in Example 1 ( Figure 3 b and Figure 3 c) In addition to the different colors, Figure 3 b and Figure 3 The printing accuracy of sample c is significantly higher than that of this embodiment, indicating that adding transparent dye can improve the printing accuracy.
[0090] See also Figure 3 d, respectively, shows the comparison of samples without dye addition (Example 5, left) and with dye addition (Example 1, right); see Figure 3 e is the infrared spectral transmittance diagram of this embodiment and embodiment 1. It can be seen from the figure that the transmittance of the PZC hydrogel without adding dye is as high as 91% in the entire visible light band, and the transmittance of the sample with added dye is 90% when the wavelength is greater than 550nm. The transmittance test sample is a hydrogel film with a thickness of 1mm. Through the comparison of transparency, it can be seen that the transparency of the hydrogel without adding dye is lower than the transparency of the hydrogel with added dye in embodiment 1.
[0091] See Table 3, which shows the test results of mechanical properties, conductive properties, and transparency of the hydrogel samples prepared in this example.
[0092] Embodiments 6 to 9
[0093] The difference between Examples 6 to 9 and Example 1 is that the water content of the precursor solution is different; the water content of the precursor solution in Examples 6 to 9 is 314.16 g, 57.6 g, 89.76 g, and 201.96 g, respectively, and the corresponding calculated water contents are 70 wt%, 30 wt%, 40 wt%, and 60 wt%, respectively. The other steps are the same.
[0094] The specific contents of the various substances in Examples 6 to 9 and the water content of the precursor solution are shown in Table 2.
[0095] Table 2: Precursor solution formulations to investigate the effect of water content on the mechanical properties of PZC hydrogels.
[0096]
[0097] Results Figure 5 a~ Figure 5 c, respectively, the mechanical properties of the hydrogels prepared from the precursor solutions with different water contents in Example 1, Example 6 to Example 9. As can be seen from the figure, as the water content increases, the mechanical properties of the hydrogel decrease.
[0098] Comparative Example 2
[0099] This comparative example is different from Example 1 which adopts a pre-dissolution method to prepare solution a to dissolve TPO. This comparative example adopts a direct dissolution method to prepare the solution, that is, directly adding TPO into the acrylamide-based aqueous solution containing PEGDA.
[0100] The specific steps are:
[0101] (1) Dissolve 10 g of PEGDA (Mw (weight-average molecular weight) = 700), 120 g of acrylamide (AM), and 12 g of zirconium nitrate pentahydrate (Zr(NO3)4·5H2O) in 120 g of deionized water, and stir continuously. This is labeled as solution a.
[0102] (2) 0.5 g chitosan (CS) and 5 g acrylic acid (AA) were added to 50 g deionized water and mixed, which was labeled as solution b.
[0103] (3) Under rapid stirring, 0.1 g of photoinitiator TPO, solution b and 0.03 g of lemon yellow were added to solution a to form a precursor solution;
[0104] The specific content of each substance in this comparative example and the water content of the precursor solution are shown in Table 2.
[0105] Results Fig.11, which are comparison diagrams of TPO being dissolved by direct dissolution method (left figure) and pre-dissolution method (right figure). The direct dissolution method involves adding TPO directly to an acrylamide-based aqueous solution. As can be seen from the figure, the TPO in the solution fails to dissolve; further, TPO can be dissolved in an acrylamide-based aqueous solution with a high water content (80wt%) by pre-dissolution method, and TPO can be completely dissolved, and the solution is transparent and clear. Specifically, pre-dissolution method: TPO is first dissolved in the cross-linking agent PEGDA (weight ratio of 1:10) to form an intermediate solution. When the intermediate solution containing the same weight of TPO as the direct method is added to the acrylamide-based aqueous solution, a clear and transparent precursor solution can be finally formed (the slightly yellow liquid in the figure is the intermediate solution, and the transparent and clear liquid is the precursor solution), indicating that TPO and the cross-linking agent have been fully dissolved.
[0106] Table 3 Mechanical properties, electrical conductivity, and transparency of the hydrogel samples of each embodiment and comparative example 2
[0107]
[0108] Referring to Table 3, the 3D printed hydrogel obtained by the technical solution of the present invention has a breaking stress of 0.51-7.25 MPa; a breaking elongation of 475-680%; a Young's modulus of 0.25-1.73 MPa; and a toughness of 2-15.85 MJ / m 3 The conductivity is 0.22-0.9 S / m, and the transparency is ≥90%. As can be seen from Table 3, the PZC hydrogel obtained in Example 1 has the best comprehensive performance.
Claims
1. A method for preparing a precursor solution of a hybrid double network hydrogel, characterized in that: The precursor solution is prepared by a pre-dissolution method; the pre-dissolution method includes using a cross-linking agent as an intermediate solvent to dissolve a photoinitiator to form an intermediate solution, and then dissolving the intermediate solution in an acrylamide-based aqueous solution and an acrylic acid aqueous solution of chitosan to obtain the precursor solution.
2. The method for preparing a precursor solution of a hybrid double network hydrogel according to claim 1, characterized in that: The photoinitiator includes one or more of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide or 2-hydroxy-2-methyl-1-phenyl-1-propanone; the crosslinking agent includes one or more of polyethylene glycol diacrylate, hydroxyethyl methacrylate, PluronicF127-diacrylate or hyaluronic acid methacrylate; and the water content of the precursor solution is 30-80wt%.
3. The method for preparing a precursor solution of a hybrid double network hydrogel according to claim 1, characterized in that: The acrylamide-based aqueous solution is obtained by dissolving acrylamide monomers in an inorganic zirconium compound aqueous solution, wherein the acrylamide monomers include acrylamide and / or acrylamide derivatives, wherein the acrylamide derivatives include any one of N,N-diethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-isopropylacrylamide, N-isobutylacrylamide, N-tert-butylacrylamide and N-cyclohexylacrylamide, and the inorganic zirconium compound is any one of zirconium oxychloride, zirconium tetrachloride, zirconium sulfate and zirconium nitrate. Preferably, the weight ratio of the inorganic zirconium compound to water in the inorganic zirconium compound aqueous solution is 1:20 to 1:4, and preferably, the weight ratio of the acrylamide monomer to water is 1:
4. ~7:3; preferably, the weight ratio of the chitosan to the acrylamide monomer is 1:1000~1:50; preferably, the weight ratio of the acrylic acid to the acrylamide monomer is 1:100~1:1, preferably, the weight ratio of the polyethylene glycol diacrylate to the acrylamide monomer is 1:100~1:20, preferably, the weight ratio of the polyethylene glycol diacrylate to the 2,4,6-trimethylbenzoyldiphenylphosphine oxide is 10:1~50:1; preferably, the concentration of the zirconium nitrate aqueous solution is 0.12 mol / L~0.47 mol / L.
4. The precursor solution prepared by the method for preparing a precursor solution of a hybrid double network hydrogel according to any one of claims 1 to 3.
5. Use of the precursor solution according to claim 4 in the preparation of hybrid double network hydrogel.
6. A hybrid double network hydrogel, characterized in that: The hybrid double network hydrogel adopts the precursor solution as described in claim 4 to carry out a double cross-linking reaction through a one-pot method to obtain the hybrid double network hydrogel. Preferably, the double cross-linking reaction includes forming a primary network through a chemical cross-linking reaction between an acrylamide monomer and a cross-linking agent under ultraviolet light irradiation; constructing a secondary network with chitosan; and establishing an in-situ physical cross-linking reaction between an inorganic zirconium compound and the secondary network to form the hybrid double network hydrogel.
7. A one-step method for preparing 3D printed double network hydrogel, characterized in that: The precursor solution as claimed in claim 4 is subjected to photocuring 3D printing to obtain a 3D printed double network hydrogel; the 3D printed double network hydrogel is customized in pattern or shape to obtain a hydrogel sample. Preferably, the method also includes adding a transparent dye to the precursor solution; preferably, the transparent dye is a water-soluble dye; preferably, the transparent dye is lemon yellow or methylene blue; preferably, the amount of the transparent dye added is 0.01~0.05wt% of the hydrogel precursor solution; preferably, the photocuring 3D printing includes layer-by-layer printing using a photocuring 3D printer; preferably, the photocuring 3D printing includes any one of stereoscopic photocuring printing, digital light processing printing, liquid crystal display photocuring printing, continuous liquid surface generation printing, two-photon polymerization printing, and projection micro-stereolithography printing.
8. A 3D printed hybrid double network hydrogel, characterized in that: The 3D printed hybrid double network hydrogel is prepared by the preparation method as claimed in claim 7; the fracture stress of the 3D printed hybrid double network hydrogel is 0.51~7.25 MPa, the fracture elongation is 475~680%, the Young's modulus is 0.31~1.73 MPa, the toughness is 1.82~15.85 MJ / m3, the conductivity is 0.75~0.90S / m, and the transparency is ≥90%.
9. Use of the method for preparing the precursor solution according to any one of claims 1 to 3, the precursor solution according to claim 4, the hybrid double network hydrogel according to claim 6, the method for 3D printing double network hydrogel according to claim 7, and the 3D printing hybrid double network hydrogel according to claim 8 in the preparation of flexible electronic devices, wherein the flexible electronic devices include flexible sensors, flexible actuators and flexible robots.
10. A flexible actuator, characterized in that: It is prepared by the preparation method as claimed in claim 7; the flexible actuator includes a customizable flexible sensor, a solvent-induced shape memory actuator and a self-sensing pneumatic actuator.